BODIPY dyes for application in the photo-oxidation of pollutants, photodynamic antimicrobial chemotherapy, and nonlinear optics - Kelechi, Lebechi Augustus (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2020)
The synthesis and structural characterization of a series of BODIPY dyes to analyze both the effects of halogenations at the 2,6-positions and the introduction of styryl groups at the 3,5-positions. The photophysical properties of these dyes were investigated to determine their suitability as singlet oxygen-generating photosensitiser dyes for application in photocatalytic degradation of azo dyes and in photodynamic antimicrobial chemotherapy (PACT). Upon halogenation, the dyes showed high to moderate singlet oxygen quantum yields. The potential utility of electrospun polystyrene (PS) nanofibres embedded with halogenated BODIPY dyes for the photocatalytic degradation of Orange G and Methyl Orange from textile industry effluents were investigated. A comparison of the singlet oxygen quantum yield of the BODIPY dyes in solution and when embedded in the PS nanofibres support demonstrates that its photosensitiser properties are maintained in the nanofibre mats. The photocatalytic degradation properties of the PS nanofibres for Orange G and Methyl Orange were determined by using a 530 nm and 660 nm light-emitting diodes. The rate of photodegradation increases with both the Orange G and Methyl Orange concentrations and follows pseudo-first-order kinetics. The PACT activities of brominated BODIPYs on Escherichia coli and Staphylococcus aureus were investigated. Log reduction values of over 9 were obtained during the photoinactivation of Staphylococcus aureus. To be able to red-shift the main spectral band of the BODIPY dyes into the therapeutic window, styryl groups were introduced at the 3,5-positions through a modified Knoevenagel condensation reaction. Because the red-shifted spectral band lies above 532 nm, the second harmonic of the Nd:YAG laser, there is very minute absorption at this wavelength. One of the novel brominated BODIPY dyes was investigated for its potential utility as optical limiting materials in nonlinear optics (NLO), and the dyes demonstrated typical nonlinear absorption behaviour characterised by reverse saturable absorption (RSA) in Z-scan measurements. Excellent optical limiting parameters were obtained for third-order susceptibility and hyperpolarisability.
Keywords: Dyes and dyeing -- Chemistry; Fluorescent probes; Fluorescence spectroscopy